Tanggapan guru dan pelajar terhadap status pendidikan geografi di sekolah-sekolah menengah Malaysia: Satu tinjauan awal - Katiman Rostam, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2005)
This paper discusses the general perception of Malaysian geography teachers and students on the status of geography as a subject matter in secondary education. Issues highlighted pertain to the strengths and weaknesses of school geography, its relevance to daily living and national development. The evaluation is based on a survey conducted in the year 2002 in the district of Hulu Langat, Selangor involving 79 secondary school teachers and 140 secondary school students of diverse background. Results of the study show that (1) Both teachers and students agree that geography is a relatively difficult subject matter; (2) Both teachers and students concur that geographical knowledge is intimately related to national development; (3) Although the majority of teachers do not distinguish geography from other school subjects, the majority of students regard it as more difficult than other subjects; and (4) While teachers agree to the idea that the geography syllabus need to be revised in order to make it more attractive to students, the latter are not willing to take up geography, thus signifying their indifferent attitude toward the subject matter